Sugar Composition of Low Molecular Weight Carbohydrate and Dietary Fibre of Some Bangladeshi Fruits - Rahman, SM Mizanur; Mahmud, Nadia; Rahim, Abu Torab MA (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.37-42